Surgical Management of a Painful Temporal Bone En Plaque Meningioma: A Case Report and Review of the Literature - Wilson, Prishae; Bhatt, Alok A.; Edgar, Mark A.; Quiñones-Hinojosa, Alfredo; Almeida, João Paulo; Raymond, Mallory (Journal of Neurological Surgery Reports, 2025)
Temporal bone en plaque meningiomas can present management challenges, particularly when accompanied by severe pain. We report the case of a 42-year-old woman who was initially diagnosed with chronic otitis media but was later found to have a painful left temporal bone en plaque meningioma. Despite conservative therapy, her pain progressed, prompting the decision to undergo surgical resection, which resulted in considerable pain relief. This report illustrates the influence of pain on surgical decision-making for temporal bone en plaque meningiomas and reviews the literature on their variable presentations and management strategies.
Keywords: case report; temporal bone; en plaque meningioma; pain; management